Effect of crack propagation on crack tip fields - F.V. Antunes; A.G. Chegini; L.M. Correia; A.L. Ramalho (Fracture and Structural Integrity)
Crack closure influences fatigue crack growth rate and must be included in the design of components. Plasticity induced crack closure is intimately linked with the crack tip plastic deformation, which becomes residual as the crack propagates. The objective here is to study numerically the effect of crack propagation on crack tip fields. The transient effect observed at the beginning of crack propagation is linked to the hardening behavior of material. The effect of mesh refinement is studied, and a singular behavior is evident, which is explained by the sharp crack associated with mesh topology, composed of a regular pattern of square elements. The plastic zone size measured perpendicularly to crack flank in the residual plastic wake is quantified and compared with literature models. Finally, the removal of material at the first node behind crack tip with load cycling was observed for plane strain state and some hardening models in plane stress state.